Efficacy of 4-methyl-7-hydroxy coumarin derivatives against vectors aedes aegypti and culex quinquefasciatus - Deshmukh, Madhavi; Pawar, Pushpa; Joseph, Mary P.; Phalgune, Usha; Kashalkar, Rajashree; Deshpande, Nirmala R. (Indian Journal of Experimental Biology, 2008)
4-Methyl-7-hydroxy coumarin is considered as a lead molecule as a biopesticide. Its mono bromo and tribromo derivatives were synthesized. Two more derivatives were synthesized by acylation. Compound 1 (3.6,8-tribromo-7-hydroxy-4-methyl-chromen-2-one) was found to be the most potent against IV(th) instar larvae of C. quinquefasciatus and A. aegypti the LC(50) being 1.49 and 2.23 ppm respectively. It showed 100% larval mortality at 25 ppm against A. aegypti and at 10 ppm against C. quinquefasciatus. Compounds 1 and 2 (3,6,8-tribromo-7-hydroxy-4-methyl-chromen-2'-oxo-2H-chromen-7-yl acetate) showed remarkable ovicidal activity. Significant reduction of 80-85%, hatching of eggs of both mosquito species was observed at the highest dose of 100 ppm. The hatched larvae showed 100% mortality in the successive instars. Compounds 3 and 4 (3-bromo-7-hydroxy-4-methyl-chromen-2-one and 3-bromo-4-methyl-2'-oxo-2H-chromen-7-yl acetate) showed moderate activity against both mosquito species.
Keywords: 4-Methyl-7-hydroxy coumarin; Aedes aegypti; Culex quinquefasciatus; Larval mortality; Ovicidal activity

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1